2012
DOI: 10.1364/aop.4.000001
|View full text |Cite
|
Sign up to set email alerts
|

Local-field effects in nanostructured photonic materials

Abstract: It is well known that the optical response of a medium depends on the local field acting on an individual emitter rather than on the macroscopic average field in the medium. The local field depends very sensitively on the microcopic environment in an optical medium. It is thus possible to achieve a significant control over the local field by intermixing homogeneous materials on a nanoscale to produce composite optical materials. A combination of local-field effects and nanostructuring provides new degrees of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 145 publications
(395 reference statements)
0
58
0
6
Order By: Relevance
“…Finally, we remark on the limitations of the shell theorem. In general, the refractive index of the QD may be different from that of the surrounding medium, leading to local field effects 40 and a possibly nontrivial dependence of the radiative lifetime on the QD radius. 19 In such cases it might seem reasonable to include additional scattering from the QD itself in the definition of B (χ ), resulting in a possibly radiusdependent correction to Eq.…”
Section: S/bmentioning
confidence: 99%
“…Finally, we remark on the limitations of the shell theorem. In general, the refractive index of the QD may be different from that of the surrounding medium, leading to local field effects 40 and a possibly nontrivial dependence of the radiative lifetime on the QD radius. 19 In such cases it might seem reasonable to include additional scattering from the QD itself in the definition of B (χ ), resulting in a possibly radiusdependent correction to Eq.…”
Section: S/bmentioning
confidence: 99%
“…Similar phenomena have been observed in the field of electromagnetic materials. Effective medium theories [1][2][3] have been developed to predict the modified bulk properties of electromagnetic media embedded with impurities in difference scenarios. Very recently, it has been observed that the bulk properties, as well as transmission behaviors of epsilon-near-zero (ENZ) media [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], are very sensitive to embedded impurities.…”
mentioning
confidence: 99%
“…[1,7,18] The effective (hyper)polarizabilities are a combination of the highest-order response and cascaded lower-order responses. When near resonance, one must be careful to account for the imaginary (nondegenerate frequency mixing, absorption, etc.)…”
Section: First-order Corrections To Microscopic Cascadingmentioning
confidence: 99%